ANALISIS PENERAPAN SISTEM INFORMASI AKUNTANSI DI UNIVERSITAS : STUDI KASUS PADA UNIVERSITAS INDONESIA - Arthaingan H Mutiha; Marsdenia Marsdenia; Andhita Yukihana (Program Pendidikan Vokasi Universitas Indonesia, 2016)
AbstractThe purpose of this study is to examine information system success of Accounting Information System based on individual performance and its impact to user satisfaction. The model used in this study is the modified IS Success Model of DeLone and McLean. The study uses primary data and data collection techniques using questionaires distributed to employee of Finance Directorate of University of Indonesia. This study used SEM approach, while analysis used LISREL software. The results showed that system quality and information quality significantly affects the individual performance while the service quality does not affect individual performance. On the other hand, the study finds that individual performance significantly affects user satisfaction.Keyword; system quality, information quality, service quality, user satisfaction, individual performance